2021
DOI: 10.3390/v13112198
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Proteomes of Porcine Macrophages and a Stable Porcine Cell Line after Infection with African Swine Fever Virus

Abstract: African swine fever virus (ASFV), causing an OIE-notifiable viral disease of swine, is spreading over the Eurasian continent and threatening the global pig industry. Here, we conducted the first proteome analysis of ASFV-infected primary porcine monocyte-derived macrophages (moMΦ). In parallel to moMΦ isolated from different pigs, the stable porcine cell line WSL-R was infected with a recombinant of ASFV genotype IX strain “Kenya1033”. The outcome of the infections was compared via quantitative mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 73 publications
0
26
0
Order By: Relevance
“…RIG-I receptor signaling was enhanced in ASFV-Georgia-infected animals and identified as impaired during ASFV infection based on metabolite analysis in vitro [ 15 , 100 ]. Other in vitro analyses described the downregulation of CD14 and CXCR2, an IL8-receptor mediating its signal via G-proteins [ 12 , 37 , 101 , 102 ]. In addition to CD14, in the present study, the downregulation of TLR2 was observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RIG-I receptor signaling was enhanced in ASFV-Georgia-infected animals and identified as impaired during ASFV infection based on metabolite analysis in vitro [ 15 , 100 ]. Other in vitro analyses described the downregulation of CD14 and CXCR2, an IL8-receptor mediating its signal via G-proteins [ 12 , 37 , 101 , 102 ]. In addition to CD14, in the present study, the downregulation of TLR2 was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Monocyte-derived macrophages (moMΦ) were isolated, selected, differentiated, and infected with ASFV, as described previously [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression profile of viral proteins was very similar in both cell lines, although cell-specific expression of some individual viral proteins did occur [ 120 ]. The authors concluded that both infection models were suitable for investigating ASFV infection biology.…”
Section: Porcine Continuous Cell Linesmentioning
confidence: 99%
“…Nevertheless, a larger number of genes were downregulated in moMΦ compared to WSL cells, suggesting that ASFV induces a host shut-off in moMΦ but no or only a weaker shut-off in WSL cells. This aspect should be taken into account in host interaction studies involving WSL [ 120 ].…”
Section: Porcine Continuous Cell Linesmentioning
confidence: 99%